2001
DOI: 10.1023/a:1013796432521
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Sanguinarine, a benzophenanthridine alkaloid, has anticancer potential through induction of cell death. We previously demonstrated that sanguinarine treatment at a low level induced apoptosis or programmed cell death (PCD) in the Bcl-2 low-expressing K562 human erythroleukemia cells, and that a high level induced blister cell death (BCD); whereas Bcl-2 overexpressing, sanguinarine-treated JM1 pre-B lymphoblastic cells displayed neither apoptosis nor BCD morphologies. Here, we report that sanguinarine-treated K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Cisplatin also induced death with features of apoptosis. In contrast, cells treated with EnAd and Ad11p usually clumped together, showed little evidence of apoptosis, and underwent sudden formation of large single membrane blisters at the time of death 9 (Movies S1, S2, S3, S4, and S5). This dramatic cellular demise, termed single blister cell death (BCD) is a typical marker of cell death by oncosis10, 11 and is thought to reflect loss of control over ion transport and consequent osmotic rupture.…”
Section: Resultsmentioning
confidence: 99%
“…Cisplatin also induced death with features of apoptosis. In contrast, cells treated with EnAd and Ad11p usually clumped together, showed little evidence of apoptosis, and underwent sudden formation of large single membrane blisters at the time of death 9 (Movies S1, S2, S3, S4, and S5). This dramatic cellular demise, termed single blister cell death (BCD) is a typical marker of cell death by oncosis10, 11 and is thought to reflect loss of control over ion transport and consequent osmotic rupture.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, we observed that treated MM cells presented an increase in cytochrome c levels in their cytosolic fraction and a concomitant loss in their mitochondrial fraction. One of the functions of cytosolic cytochrome C is to interact with apoptotic protease-activating factor-1 (APAF-1) and procaspase 9 in the presence of ATP to form the multimeric complex, apoptosome, which in turn activates caspase 9 and induce apoptosis (34). Since we show that caspase 9 expression was efficiently increased in MM cells in response to SNG treatment, we suggest that SNG-mediated apoptosis in MM cell lines involves mitochondria-mediated caspase activity.…”
Section: Discussionmentioning
confidence: 99%
“…In similarity to berberine, sanguinarine also have antimicrobial, antioxidant and anti-inflammatory properties (Firatli et al, 1994 ). The cytotoxic and cytostatic effects of sanguinarine on a variety of human cancer cells, including human epidermoid carcinoma, erythroleukemia, prostate cancer, pancreatic carcinoma, colon cancer, breast cancer, lung cancer, promyelocytic leukemia, and bone cancer (Weerasinghe et al, 2001a , b ; Matkar et al, 2008 ; Vrba et al, 2009 ; Park et al, 2010 ), have been reported. Sanguinarine exhibits the highest cytotoxicity among benzophenanthridine alkaloids (Slaninová et al, 2001 ; Vogel et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%